Combatting corruption: understanding anti-corruption initiatives in Malaysia. By Anis Yusal Yusoff, Sri Murniati, and Jenny Gryzelius. Kuala Lumpur: Institute for Democracy and Economic Affairs, 2013, pp. 183, ISBN: 978-967-10094-7-5 - Mohd. Adnan, Normala (IIUM Press, 2015)
Combatting Corruption: Understanding Anti-corruption Initiatives in Malaysia is a new addition to the available works on corruption in Malaysia. This work reinforces the belief that corruption is undeniably a complex problem that is very difficult to eradicate. Referring to many studies and discussions with governmental and non-governmental organisations and other relevant participants, the book examines the extent of the Malaysian government’s success in implementing coherent strategies and initiatives to combat corruption. This sets out the purpose and direction of the book, which is to help key stakeholders evaluate previous initiatives and learn lessons while at the same time encourage critical discussion among those involved in promoting integrity and fighting corruption. The authors adopt the view that corruption requires coherent strategies for prevention and deterrence, as compared to existing efforts in Malaysia that focus on detection. In arguing this, the authors seem to support Kaufman’s findings (2003), which claim that without targeted anti-corruption initiatives, the development of appropriate laws and agencies, and strengthening them, would have limited effect on combating corruption (Kaufman, D., Governance crossroads, in P. Cornelius, K. Schwab, & M. E. Porter (Eds.), Global Competitiveness Report 2002-2003. New York: Oxford University Press, 2003).